(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The aim of this paper is to highlight one of the risks facing the banking system in general and the Iraqi in particular, both Islamic and commercial, resulting from the low liquidity of banks from their safe levels, which expose the bank to a number of effects, especially when exposed to sudden withdrawals through measuring and analyzing the banking liquidity risk of banking and the statement The most important means used to processing these risks, including the adequacy of capital according to the Basel II Accord. Two banks, the National Islamic Bank and the Commercial Bank of Iraq, were selected and the indicators of liquidity risk were used. Statement of the Effect of the Capital Adequacy Tool as a Tool that Contributes to the Absorption of Banking Risks and their Effects in Mitigating Liquidity Risk The indicators were analyzed and tested by testing F, P-value and impact statement through the R2 parameter using the ANOVA analysis. There is a significant effect of the capital adequacy ratio on the liquidity risk of banks and both banks to varying degrees on the basis of which the alternative hypothesis was accepted. The paper also reached the recommendations of the most important of which is the need to achieve a balance between the size of the balances utilized in the various banking fields and what is maintained, Exceed the capital adequacy ratios for the specified rates by the Central Bank of Iraq.